Postnatal Depression in Malaysia: Perspectives of Stakeholder on Awareness Medium - Alimuddin, Aishah Siddiqah; Mohd Daud, Tuti Iryani; Silim, Umi Adzlin; Mohd Balwi, Mohd Abdul Wahab Fatoni; Zainuddin, Ani Amelia; Midin, Marhani; Zakaria, Hazli (IIUM Medical Journal Malaysia, 2021)
INTRODUCTION: Postnatal depression is a highly prevailing illness, yet underdiagnosed. Untreated, it carries a transgenerational impact, and therefore promoting awareness for it has to be of high priority. This research explored the elements of an educational tool to develop awareness for postnatal depression as preferred by stakeholders. MATERIALS AND METHOD: A descriptive qualitative approach using semi-structured face-to-face interviews were conducted, where nine participants were recruited via purposive sampling from a university hospital in Malaysia. Interviews with each participant were audio-recorded and transcribed to verbatims. Emergent themes were identified during the analysis. RESULTS: Four consistent themes regarding elements for an educational tool were derived as follows: Foundations of the tool, Illness circumstances, Support bases, and Matters of perspective. CONCLUSION: An educational video within the local setting should involve the usage of a short emotionally driven video, highlighting illness- and treatment-related content, and addressing the preference and concerns of women within the religious and cultural context. The use of edutainment as an educational tool is replicable and has a high outreach even to those who are illiterate. The findings can be used in the tailored development of an educational video on postnatal depression which will benefit local women by creating awareness and encouraging early help-seeking.